Estimation of gillnet selectivity for shabbout (Arabibarbus grypus Heckel, 1843) - Yüksel, Fahrettin; Demirol, Ferhat; Gunduz, Fatih; Coban, Mehmet Zulfu (Parlar Scientific Publications, 2020)
In this study, it was aimed to determine the selectivity properties of the gillnets used for Shabbout (Arabibarbus grypus Heckel, 1843) in Keban Dam Lake, Turkey. Experiments were carried out at 3 different stations of the dam lake using 5 monofilament gillnets with 40, 50, 60, 70, 80 mm nominal mesh size (bar length). A total of 510 target species between 38 and 79.2 cm in total length were caught in 47 catching trials. The select method was used to estimate the selectivity parameters. When the model deviations were compared, the lowest deviation (183.6104) was observed to be given by the lognor-mal model. According to this model, optimum catch lengths of nets which have 40, 50, 60, 70, 80 mm mesh size determined as 40.12, 50.15, 60.18, 70.21, 80.24 cm and their spread values 3.03, 3.79, 4.55, 5.30, 6.06 cm, respectively. The differences between the length frequencies of the fish caught by all nets were found to be significant according to the Kolmo-gorav-Smirnov test. Minimum catch size of Shabbout is notified as 45 cm in Turkey. According to results of this study, gillnets with 50 mm and above mesh size do not cause an overfishing on Shabbout stocks. © by PSP
Keywords: Arabibarbus grypus; Gillnet selectivity; Keban Dam Lake; Select method; Shabbout